10.5k views
10 votes
Please please please helpppp, (please show work if you can)

Please please please helpppp, (please show work if you can)-example-1

1 Answer

5 votes

Answer:

∴ m∠KIJ = 18° and m∠HIJ = 50°

Thus, option a is correct.

Explanation:

From the figure, it is clear that:

m∠KIH = m∠HIJ + m∠KIJ

Given

  • m∠KIH = 68°
  • m∠KIJ = (2x + 6)°
  • m∠HIJ = (9x - 4)°

now substituting m∠KIH = 68°, m∠KIJ = (2x + 6)° and m∠HIJ = (9x - 4)° in the equation

m∠KIH = m∠HIJ + m∠KIJ

68° = (2x + 6)° + (9x - 4)°

switch sides


\left(2x+6\right)+\left(9x-4\right)=68

Group like terms


2x+9x+6-4=68


11x+2=68

Subtract 2 from both sides


11x+2-2=68-2

Simplify


11x=66

Divide both sides by 11


(11x)/(11)=(66)/(11)

Simplify


x=6

Hence, the value of x = 6

Therefore,

m∠KIJ = (2x + 6)° = 2(6) + 6 = 12 + 6 = 18°

m∠HIJ = (9x - 4)° = 9(6) - 4 = 54 - 4 = 50°

∴ m∠KIJ = 18° and m∠HIJ = 50°

Thus, option a is correct.

User Amit Chauhan
by
5.2k points